2020
DOI: 10.1111/jcmm.16205
|View full text |Cite
|
Sign up to set email alerts
|

The role of androgen and its related signals in PCOS

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women at reproductive age. However, the underlying pathogenic mechanisms have not been completely understood. Hyperandrogenism is an important clinic feature in patients with PCOS, suggesting its pathologic role in the development and progression of PCOS. However, the actual role of androgen and the related signals in PCOS and PCOS‐related complications have not yet been clarified. In this review, we surveyed the origin and effects of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 108 publications
(192 reference statements)
0
55
0
2
Order By: Relevance
“…Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism, irregular menses, hirsutism, anovulation, dyslipidemia, hypertension, insulin resistance, and polycystic ovaries when other etiologies are excluded [ 1 – 3 ]. There are 10–15% of reproductive-aged women affected with PCOS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism, irregular menses, hirsutism, anovulation, dyslipidemia, hypertension, insulin resistance, and polycystic ovaries when other etiologies are excluded [ 1 – 3 ]. There are 10–15% of reproductive-aged women affected with PCOS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are 10–15% of reproductive-aged women affected with PCOS [ 4 ]. Up to 60–80% of women with PCOS appear hyperandrogenism [ 1 ]. Hyperandrogenism is a medical condition characterized by excessive levels of androgens in the periphery or systemically.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperandrogenemia is the main endocrine characteristic of PCOS. Hyperinsulinemia and IR are considered to be the main causes of hyperandrogenemia [ 35 , 36 ], while excessive androgen leads to increased levels of LH and FSH [ 37 ]. In PCOS, theca cells and granulosa cells overexpress mRNA encoding enzymes involved in steroidogenesis, including androgen receptor, CYP11, CYP17, and CYP19, and this can lead to disturbances in ovarian hormone synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is known as the most common endocrine/metabolic disorder in women of reproductive age, where it is reported that PCOS affects 5 to 26 percent of women (based on the applied diagnostic criteria) around the world. 1 , 2 PCOS was found to be associated with different diseases such as metabolic syndrome, type 2 diabetes, hypertension, cardiovascular diseases and even ovulatory infertility. 3 , 4 There are four distinguished subtypes; inflammatory, hidden cause and finally, pill‐induced PCOS and insulin‐resistant (the most prevalent type).…”
Section: Introductionmentioning
confidence: 99%